Biodegradable nanoparticles loaded with tetrameric melittin: preparation and membrane disruption evaluation - González Horta, Azucena C.; Matamoros Acosta, Arely; Chávez Montes, Abelardo; Castro Ríos, Rocío; Lara Arias, Jorge (2017)
Abstract. Melittin is the main component of bee venom consisting of 26 amino acids that has multiple effects, including antibacterial, antiviral and anti-inflammatory in various cell types. This peptide forms pores in biological membranes and triggers cell death. Therefore it has potential as an anticancer therapy. However, the therapeutic application of melittin is limited due to its main side effect, hemolysis, which is especially pronounced following intravenous administration. In the present study, we formulated tetrameric melittin-carrying poly-D,L-lactic-co-glycolic acid nanoparticles (PLGANPs) and analyzed the lytic activity of this system on liposomes that resembles breast cancer cells. Tetrameric melittin binds avidly to PLGA-NPs with an encapsulation efficiency of 97% and retains its lytic activity demonstrating the effectiveness of PLGA-NPs as nanocarriers for this cytolytic peptide. Key words: Melittin — PLGA nanoparticles — Liposomes — Leakage — Fluorescence — Circular dichroism